Mental health status of students' parents during COVID-19 pandemic and its influence factors. Issue 4 (21st July 2020) - Wu, Mengting; Xu, Wenyan; Yao, Yuhong; Zhang, Lei; Guo, Lei; Fan, Juan; Chen, Jue
Abstract : Background: During the outbreak of COVID-19, the national policy of home quarantine may affect the mental health of parents. However, few studies have investigated the mental health of parents during the COVID-19 pandemic. Aims: To investigate the depression, anxiety and stress of the students' parents during the COVID-19 pandemic, and to explore the influence factors, especially the influence of social support and family-related factors. Methods: The Generalised Anxiety Disorder-7, Patient Health Questionnaire-9, Perceived Stress Scale-10 and Social Support Rating Scale were applied to 1163 parents to measure the parents' depression, anxiety, stress and social support. Results: (1) The detection rates of depression and anxiety in parents were 6.1% and 4.0%. The depression, anxiety and perceived stress of parents in central China were significantly higher than those in non-central China. The anxiety of college students' parents was lower than that of parents of the primary, middle and high school students. The depression, anxiety and perceived stress of parents with conflicts in the family were significantly higher than those with a harmonious family. Other factors that influence parents' depression, anxiety and perceived stress include marital satisfaction, social support, parents' history of mental illness and parenting style, etc. (2) The regression analysis results showed that perceived stress, social support, marital satisfaction, family conflicts, child's learning stage as well as parents' history of mental illness had significant effects on parents' anxiety and depression. Conclusion: During the COVID-19 pandemic, the mental health of parents was affected by a variety of factors. Good marital relationships, good social support, family harmony and parents without a history of mental illness may be protective factors for parents' mental health, while perceived stress and child in middle or high school are risk factors for parents' mental health.